PERAN LEMBAGA ADAT DALAM PENGATURAN TANAH ULAYAT DI DESA RUIS KECAMATAN REOK KABUPATEN MANGGARAI - Ngambol, Vinsensius Dedewidjayanto; Ajis Djaha; Pandie, Ardy (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
This study aims to describe the role of customary institutions in the regulation of ulayat land in Ruis Village, Reok Subdistrict, Manggarai Regency. Customary institutions play a crucial role in regulating, allocating, and resolving disputes over ulayat land through traditional values, customary law, and consensus-based mechanisms. However, since the implementation of government programs such as Gempar and Gerbades during the reform era, the authority of customary institutions has weakened due to the shift of land management rights from customary authorities to individual community members. This research employs a qualitative case study approach, with data collected through interviews, observations, and documentation. The findings reveal a significant decline in the role of customary institutions in ulayat land management, particularly in land allocation, boundary control, and conflict resolution. Both internal and external factors contribute to this decline, including weak leadership regeneration, lack of written customary law, and the growing dominance of formal governmental systems.